2017
DOI: 10.1002/jor.23736
|View full text |Cite
|
Sign up to set email alerts
|

Labral calcification in end‐stage osteoarthritis of the hip correlates with pain and clinical function

Abstract: ALH fibrocartilage appears to be particularly prone to calcification, which may explain higher pain levels in individuals with a high degree of ALH calcification independent of age and histological degeneration. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1248-1255, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 41 publications
(86 reference statements)
2
26
0
1
Order By: Relevance
“…Cartilage degeneration was associated with the presence of macrophages (CD68+ cells) in the synovium, consistent with previous reports [46,49]. In addition, cartilage lesions were also associated with increased calcium crystal deposition in the labrum, as previously shown for end-stage HOA [24].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Cartilage degeneration was associated with the presence of macrophages (CD68+ cells) in the synovium, consistent with previous reports [46,49]. In addition, cartilage lesions were also associated with increased calcium crystal deposition in the labrum, as previously shown for end-stage HOA [24].…”
Section: Discussionsupporting
confidence: 91%
“…We also found that the presence of labral crystal calcium deposition was associated with lower pre-operative HOOS and, interestingly, with worst post-operative symptoms independent from age and radiographic severity. The same observation was previously reported [24] in end-stage OA, supporting the hypothesis that labral calcification might play a key role in hip pain and symptoms both in FAI and endstage OA. A higher local concentration of calcium crystal deposition in the labrum could lead to increased release of nociceptor stimulating substances [26,27] within the fibrocartilage tissue, which densely innervated [42].The presence of labral calcification is also associated with a worst labral matrix integrity and subsequent degradation of the acetabular cartilage as described by Song et al [43],thus possibly jeopardizing the effect of the surgical repair [41].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…2 Before arthroscopic treatment, each patient failed an extensive course of conservative management, commonly including rest, activity modification, physical therapy, and diagnostic/therapeutic intra-articular hip corticosteroid injections. 12 The risks and benefits of hip arthroscopy were discussed with each patient by the senior author (G.D.D. ), and informed consent was obtained prior to surgery.…”
Section: Indications For Surgerymentioning
confidence: 99%
“…Nach klinischen Standardscores erhoben, korreliert die Menge des Knorpelmineralgehalts an Hüfte und Kniegelenk mit dem subjektiv empfundenen Schmerzniveau [15,16]. Wenn man die Lokalisation der ektopen Mineralisation weiter differenziert und die Kalzifikation des Labrum acetabulare von der Kalzifikation des Gelenkknorpels im Hüftgelenk separat betrachtet und parallel analysiert, wird evident, dass der Faserknorpel des Labrums besonders anfällig für Kalzifikation ist (Faktor 1,55 mehr Mineralgehalt gegenüber dem hyalinen Gelenkknorpel) und dass die Labrummineralisation stärker als die Gelenkknorpelmineralisation mit dem subjektiven Schmerzniveau korreliert [17,18].…”
Section: Schmerz Und Chondrokalzinoseunclassified